PATOBA: RITUAL PERALIHAN PADA ORANG BAJO DI DESA LATAWE KECAMATAN NAPANO KUSAMBI KABUPATEN MUNA BARAT - Dalnia Dalnia; Wa Ode Sitti Hafsah; La Ode Aris (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the process of implementing the patoba ritual as well as the values contained in the patoba ritual carried out by the Bajo in Latawe Village, District of Napano Kusambi, West Muna Regency. This research is descriptive-qualitative research with data collection techniques through involved observation and in-depth interviews. The results showed that the patoba ritual was one of the cultural heritage traditions born in Latawe Village, West Muna Regency. Patoba is a transitional ritual from childhood to adolescence. The transition period is the most important period in the stage of development of children because the transition period is the basis of personality that was built for all his life. The process of implementing the patoba ritual in Bajo people in Latawe Village, Napano Kusambi District, West Muna Regency begins with preparing ritual materials. Whereas the values contained in the patoba ritual are the value of forgiveness, the value of recognition that the Prophet Muhammad is the messenger of Allah, the value of obedience to the father and mother, the value of respect for the older, the value of compassion, the value of health, the value of salvation, the value of togetherness, the value of togetherness, value forgiveness, and courtesy values. Keywords: ritual, transitional, value, Bajonese.